Ultimum Remedium as a State Loss Recovery Mechanism in Corporate Tax Crimes - Astuti, Dwi; Latif, Abdul; Suasoongern , Sineenart (Journal Evidence Of Law, 2025)
The ultimum remedium principle in tax criminal law is designed as the last limit in law enforcement, which is only used when administrative efforts are no longer effective. However, in the practice of handling corporate tax crimes in Indonesia, this principle is often ignored, so that punishment becomes the first step instead of the last resort. This research aims to analyze the effectiveness of the ultimum remedium as a mechanism to recover state losses and assess the extent to which its implementation reflects the principles of justice and fiscal efficiency. Using a normative juridical approach with the support of empirical data from court decisions and interviews, this research finds that the principle has not been applied consistently, and tends not to have a significant impact on state financial recovery. As a novelty, this research proposes a restorative fiscal justice approach model that places the ultimum remedium as an active strategy to recover losses, not just a criminal limitation principle. The findings are expected to strengthen the direction of economic criminal law reform that is more proportional, efficient, and adaptive to the country's fiscal needs.